Effectiveness of lower limb rehabilitation protocol using mobile health on quality of life, functional strength, and functional capacity among knee osteoarthritis patients who are overweight and obese: A randomized-controlled trial - Muhammad Tariq Rafiq,; Mohamad Shariff Abdul Hamid,; Eliza Hafiz, (Archives of Rheumatology, 2023)
Objectives: This study aims to investigate the effectiveness of the lower limb rehabilitation protocol (LLRP) using mobile health (mHealth) on quality of life (QoL), functional strength, and functional capacity among knee OA patients who were overweight and obese. Patients and methods: Between August 2019 and November 2020, a total of 96 patients (42 males, 54 females; mean age; 52.9±4.8 years; range, 40 to 60 years) were randomized into either the rehabilitation group with mobile health (RGw-mHealth) receiving reminders by using mHealth to carry on the strengthening exercises of LLRP and instructions of daily care (IDC), the rehabilitation group without mobile health (RGwo-mHealth) following the strengthening exercises of LLRP and instructions of daily care (IDC) and control group (CG) only following the IDC for duration of 12 weeks. The reminders for using mHealth were provided two times a day for three days a week. Primary outcome measures were QoL assessed by the Western Ontario and McMaster Universities Osteoarthritis Index summary score, and functional strength by five-repetition sit-to-stand test. Secondary outcome measure was functional capacity assessed by the Gait Speed Test. The assessments of QoL, functional strength, and functional capacity were taken at baseline and post-test after 12 weeks of intervention. Results: After 12 weeks of intervention, the patients in all three groups had a statistically significant improvement in QoL within groups (p<0.05). Patients in the RGw-mHealth and RGwo-mHealth had a statistically significant improvement in functional strength and walking gait speed within groups (p<0.05). The pairwise between-group comparisons (Bonferroni post-hoc test) of the mean changes in QoL, functional strength, and functional capacity at post-test assessments revealed that patients in the RGw-mHealth had a statistically significant greater mean change in QoL, functional strength and functional capacity relative to both the RGwo-mHealth and CG (p<0.001). Conclusion: The improvement in QoL, functional strength, and functional capacity was greater among patients in the RGw-mHealth compared to the RGwo-mHealth or CG.